The child ecosystem and childhood pulmonary tuberculosis: A South African perspective. Issue 7 (25th March 2021) - DeAtley, Teresa; Workman, Lesley; Theron, Grant; Bélard, Sabine; Prins, Margaretha; Bateman, Lindy; Grobusch, Martin P.; Dheda, Keertan; Nicol, Mark P.; Sorsdahl, Katherine; Kuo, Caroline; Stein, Dan J.; et al.
Abstract: Introduction: This study investigates drivers of childhood pulmonary tuberculosis (PTB) using a childhood ecosystem approach in South Africa. An ecosystem approach toward identifying risk factors for PTB may identify targeted interventions. Methods: Data were collected as part of a prospective cohort study of children presenting at a primary care facility or tertiary hospital with possible TB. Characterization of the childhood ecosystem included proximal, medial, and distal determinants. Proximal determinants included child characteristics that could impact PTB outcomes. Medial determinants included relational factors, such as caregiver health, which might impact interactions with the child. Distal determinants included macro‐level determinants of disease, such as socioeconomic status and food insecurity. Children who started on TB treatment were followed for up to 6 months. Multivariate regression models tested independent associations between factors associated with PTB in children. Results: Of 1202 children enrolled, 242 (20%) of children had confirmed PTB, 756 (63%) were started on TB treatment, and 444 (37%) had respiratory conditions other than TB. In univariate analyses, childhood malnutrition and caregiver smoking were associated with treated or confirmed PTB. In multivariate analyses, proximal factors, such as male gender and hospitalization, as well as low socioeconomic status as a distal factor, were associated with PTB. Conclusions: Interventions may need to target subgroups of children and families with elevated proximal, medial, and distal risk factors for PTB. Screening for risk factors, such as caregiver's health, may guide targeting. The provision of social protection programs to bolster economic security may be an important intervention for attenuating childhood exposure to risk factors.